2015
DOI: 10.1186/s12917-015-0581-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and diffusion tensor magnetic resonance imaging of the sheep brain

Abstract: BackgroundAn ovine model can cast great insight in translational neuroscientific research due to its large brain volume and distinct regional neuroanatomical structures. The present study examined the applicability of brain functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) to sheep using a clinical MR scanner (3 tesla) with a head coil. The blood-oxygenation-level-dependent (BOLD) fMRI was performed on anesthetized sheep during the block-based presentation of external tactile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…2, Fig. 3), functional imaging [8], neurovascular structure [9] as well as sleep homeostasis [10], making it an excellent specimen in translational neuroscience. Cadaveric sheep brains (Fig.…”
Section: Ovine Modelsmentioning
confidence: 99%
“…2, Fig. 3), functional imaging [8], neurovascular structure [9] as well as sleep homeostasis [10], making it an excellent specimen in translational neuroscience. Cadaveric sheep brains (Fig.…”
Section: Ovine Modelsmentioning
confidence: 99%
“…Current developments are under way in our institution to deliver adapted visual stimuli with dedicated instrumentation (Sonnay et al, 2018). A previous study in sheep (Lee et al, 2015) reported robust visual activation in the primary visual cortex (V1) with BOLD responses around 2%. However, in this previous study, sheep were anesthetized with N-methyl-D-aspartate (NMDA) receptor antagonist, Telazol, in order to precisely avoid alteration of cerebral blood hemodynamic responses due to volatile anesthesia such as ISO.…”
Section: Impact Of Isoflurane Anesthesia On Bold Fmri Responses In Sheepmentioning
confidence: 99%
“…In order to study sexual behaviour and hormonal status in the sheep brain, functional magnetic resonance imaging (fMRI) demonstrated valuable features (Ella et al, 2019). Recently, a few studies explored MRI functional possibilities in the sheep brain (Lee et al, 2015;Pieri et al, 2019) demonstrating reproducible and translatable features at clinical magnetic fields (1.5T and 3T). To the best of our knowledge, cerebral perfusion MRI has not been reported in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Walker et al () gave evidence to indicate a role of sleep in Off‐line memory processing. Lee et al () applied fMRI and DTI techniques and they found activations in the sensorimotor and visual areas during sleep. Christian et al () investigated the resting‐state connectivity using independent component analysis (ICA).…”
Section: Introductionmentioning
confidence: 99%